Ultrasonographic findings of intrascrotal testicular torsion at the early stage in a rabbit model - ERDOĞAN, G.; AKKUŞ, T.; PEKER, C.; UÇAR, E.H. (Journal of the Hellenic Veterinary Medical Society, 2021)
Intrascrotal testicular torsion (ISTT) cases are rarely seen in companion animals, harming both testicular functions. These are considered reproductive emergency cases and need acute surgical intervention. In this research, early scrotal ultrasonographic findings were assessed in a rabbit model. Unilaterally, complete clockwise torsion was inducted in the left testicles of eight healthy pubertal male rabbits. The right testicle of each animal was considered as control. B-mode and Doppler ultrasonography (USG) was performed preoperatively (-1st) and postoperatively (2,4,6, and 24th) hours (h). At the first two hours, swelling, cyanosis, hypothermia, and pain symptoms were observed in all rabbits (100%). Reactive hydrocele was sonographically detected at 2-h (12.5%; 1/8), 4-6, and 24-h (50%; 4/8), respectively. At 2nd h, hyperechogenic whirlpool sign was remarkable in transversal and sagittal scans of the spermatic cord in all cases (100%). At 6th h, increased echogenicity of the spermatic cord and testicular parenchyma were also observed in all torsed testes (100%). Except for the scrotal capillary vessels in the distal part of torsion, testicular and epididymal blood flow were absent in all rabbits (100%). Increased pulsatility index (PI) at the second h and decreased resistance index (RI) at the 4th and 6th h in the control group (P<0.05) was observed. At the end of the study, RI was increased at 24th h in both groups (P<0.05). The mild hydrocele and whirlpool signs are clear and remarkable diagnostic findings of ISTT cases in rabbits. By twisting at the spermatic cord, increased echogenicity and absence of blood flow from the twisted area to the distal part of the spermatic cord help the differential diagnosis. The torsion causes the increasing RI in contralateral testicular perfusion after 24 hours of the event. In conclusion, testicular echogenicity, whirlpool signs, visibility of the blood flow, and its spectral waveform features are useful measurements in diagnosing ISTT cases. Moreover, the time of torsion and prognosis may also be estimated.